Efficacy and Survival Analysis of Radiotherapy for Internal Mammary Lymph Nodes After Modified Radical Mastectomy for T1-3N3M0 the Lateral Quadrant Breast Cancer - Han X; Jiang D; Zhu C; Li D; Yin H (Breast Cancer: Targets and Therapy)
Xiumei Han,1,* Die Jiang,1,* Chaomang Zhu,2,* Duojie Li,1 Hongmei Yin1 1Department of Radiotherapy, The First Affiliated Hospital of Bengbu Medical University, Bengbu, Anhui, 233000, People’s Republic of China; 2Anhui Provincial Key Laboratory of Tumor Evolution and Intelligent Diagnosis and Treatment, Bengbu Medical University, Bengbu, Anhui, 233000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hongmei Yin, Department of Radiotherapy, The First Affiliated Hospital of Bengbu Medical University, Bengbu, Anhui, 233000, People’s Republic of China, Tel/Fax +86 182 2655 8221, Email yhm062573@163.comPurpose: This study aimed to investigate the efficacy and survival analysis of internal mammary lymph nodes (IMLNI) radiotherapy after modified radical mastectomy for T1-3N3M0 The lateral quadrant breast cancer.Materials and Methods: A total of 124 patients who underwent adjuvant radiotherapy after modified radical mastectomy for breast cancer in the First Affiliated Hospital of Bengbu Medical University were included. The patients were divided into the internal mammary lymph node (IMLN) irradiation group, and sixty-two patients received postoperative chest wall + upper and infraclavicular lymph nodes + IMLNI,sixty-two patients in the non-IMLN irradiation group received postoperative radiotherapy to the chest wall + upper and infraclavicular lymph nodes. The radiotherapy dose was 45– 50GY, The disease-free survival rate (DFS), survival rate (OS), local recurrence rate (LRR), distant metastasis rate (DM), and adverse radiation reactions were analyzed.Results: Median follow-up was 56 months (range 12– 96). The 5-year OS in the IMLNI group and the non-IMLNI group were 80.6% and 79.8% (P> 0.05), DFS was 62.9% and 59.7% (P> 0.05), LRR was 22.6 and 21.0% (P> 0.05), and DM was 25.8% and 33.9% (P> 0.05), respectively. Multifactorial showed that T stage, PR status, vascular cancer embolism, it was an independent prognostic factor affecting the 5-year OS of patients, and PR expression status (P=0.038) was an independent prognostic factor affecting the 5-year LRR.Conclusion: For breast cancer patients located in the outer quadrant and more than 9 axillary lymph node positives, increasing IMNI failed to improve the 5-year prognosis of the patients, and for patients with late N stage, PR receptor-negative, and vascularity cancer thrombosis positive, the 5-year OS of breast cancer postoperative patients could be reduced, and the PR receptor positivity could reduce the 5-year LRR of patients. There was no significant difference in 5-year late radiation adverse effects between the IMLNI and non-IMLNI groups.Keywords: breast cancer, internal mammary lymph node irradiation, radiotherapy, survival rate, retrospective study